Phenology of Flowering Time and Flowering Duration of Tomato Plants (Solanum lycopersicum L.) in Kamang Magek District and Padang City - Azizah, Salum; Vauzia, Vauzia; Chatri, Moralita; Putri, Irma Leilani Eka (Jurnal Biologi Tropis, 2025)
Tomato (Solanum lycopersicum L.) is one of the horticultural commodities with high economic value whose growth is greatly influenced by environmental conditions. This study aims to examine the phenology of tomato plants, including the time of flowering and flowering duration in different environmental conditions as a basis for developing more effective cultivation techniques. The study was conducted in two locations, namely Kamang Magek District and Padang City, with 20 replications per location. Phenology observations were carried out on the time of flowering and flowering duration of tomato plants, and the data obtained were analyzed using the t-test at a significance level of 5%. The results showed a significant difference between the two locations, where the average time of flowering in Kamang Magek District was 38.5 days after planting (DAP) with a flowering duration of 10.85 days, while in Padang City the time of flowering occurred at 75.8 DAP with a flowering duration of 30.3 days. This difference indicates that environmental conditions in Kamang Magek District are more supportive of accelerating the flowering phase with a shorter flowering cycle.